Impact of the organizational innovations in the performance of manufacture companies in Costa Rica and Germany. A case study - Oviedo Agüero, Daniel (2015)
This investigation analyzes the direct and indirect impact produced by the organizational innovations implemented by the company. This study approaches the topic from a qualitative perspective through a case study analysis. Five study subjects were selected: three companies within an Industrial Corridor in Costa Rica and two companies from the federal state of Baden- Württemberg in Germany. As a result, the organizational innovation has a positive effect in the company’s performance, and it was possible to identify both similarities and differences between countries and the implemented innovations. Another finding suggests that the firm’s strategy plays a key role in defining future results of the organizational innovation.